2020
DOI: 10.1021/acsomega.0c02421
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Antiviral Bioactivity, and Mechanism of the Ferulic Acid Ester-Containing Sulfonamide Moiety

Abstract: Tobacco mosaic virus (TMV) has caused huge economic losses to tobacco, pepper, cucumber, and ornamental crops all over the world. However, few effective antiviral agents were developed and applied to control such plant disease. It is challenging to find an anti-TMV agent which is highly effective, less toxic, and environmentally friendly. In this work, a series of ferulic acid ester-containing sulfonamide moieties were designed and synthesized, and the antiviral activities of these compounds against TMV were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…In recent years, other authors considered TMV CP an important target for screening viral agents against tobamoviruses [ 90 , 97 , 104 , 105 , 106 , 107 ]. Careful literature overview highlighted several in silico studies based on the crystal structure of TMV CP (PDB code 1ei7) [ 39 , 72 , 73 , 89 , 91 , 94 , 97 , 105 , 106 , 107 ]. Due to the high conservation of the tobamovirus CP sequences [ 108 ] in this study, we considered the TMV CP sequence as a template.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, other authors considered TMV CP an important target for screening viral agents against tobamoviruses [ 90 , 97 , 104 , 105 , 106 , 107 ]. Careful literature overview highlighted several in silico studies based on the crystal structure of TMV CP (PDB code 1ei7) [ 39 , 72 , 73 , 89 , 91 , 94 , 97 , 105 , 106 , 107 ]. Due to the high conservation of the tobamovirus CP sequences [ 108 ] in this study, we considered the TMV CP sequence as a template.…”
Section: Discussionmentioning
confidence: 99%
“…Activity of plant compounds against phyto-viruses has been reported [ 30 , 31 , 32 ]. Plant phenolic compounds are involved in plant defense [ 33 , 34 ] and show several properties against a wide spectrum of plant pathogens [ 35 , 36 ], specifically against various viruses, including tobamoviruses [ 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…FA is required for the stiffness of the cell wall and acts as an antioxidant, antimicrobial, anticarcinogenic, antiviral, and enzyme activity modulator [82]. The application of ferulic acid amide derivatives at 500 µg/mL exhibited higher protective and curative activities against TMV than the ribavirin (control) compound [83,84]. Caffeic acid is a hydroxycinnamic acid with many acrylic functional groups and is most commonly produced from plants.…”
mentioning
confidence: 99%
“…According to the classic literature method ( Ren et al, 2020 ), the activity of the target compound H1–H23 on TMV was tested. Preliminary bioactivity showed that most of the compounds exhibited a good inhibitory effect on TMV at 500 μg/ml.…”
Section: Resultsmentioning
confidence: 99%